Chapter 10 Evolution of Host Resistance and Parasitoid Counter-Resistance - Kraaijeveld, A; Godfray, C (2009)
By their nature, parasitoids will exert a selection pressure on their hosts to evolve a mechanism through which to resist parasitoid attack. In turn, such a resistance mechanism will lead to parasitoids evolving counter-resistance. In this chapter, we present an overview of the research on the (co)evolutionary interaction between Drosophila and their parasitoids, with the main focus on the cellular immune response of D. melanogaster, and the counter-resistance mechanism of one of its main parasitoids, Asobara tabida. A key aspect of this interaction is the existence of genetic variation: in the field, host resistance and parasitoid counter-resistance vary, both between and within populations. Host resistance and parasitoid counter-resistance are costly, and both these costs turn out to be density dependent. These tradeoffs can explain the existence of genetic variation. We briefly touch upon behavioral aspects of the interaction and the parasites and pathogens that the parasitoids themselves suffer from. We end this chapter by considering the data coming from gene chip experiments: early indications suggest that the genes involved in the actual immune response against parasitoids are mostly different from the genes involved in the evolution of resistance. © 2009 Elsevier Ltd. All rights reserved.